A review of criteria as basis for evaluation of health instruction program in the elementary grades - Fabreo, Rosalina (Aquino) 1916- ([Quezon City s.n], 1968)
The purpose of the study is to review the criteria for evaluating the health instruction program in the elementary grades. The study specifically answers this question: What criteria are there for evaluating the administration and supervision of the school health instruction program, its objectives, content, learning experiences, methods and procedures in teaching in the elementary grades, staff development and evaluation program?
Thesis (M.A.T.Health)--University of the Philippines
Keywords: Health education (Elementary).